Життєздатність Betula pendula Roth. в урбосистемі м. Кривого Рогу - Korshikov, I.I.; Petrushkevych, Yu.M. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2017)
We investigated the viability of silver birch (Betula pendula Roth.) in the urbanized system of Krivyi Rih. The largest biometric indicators of the 34–36 year old trees are marked in plantations growing in the arboretum of botanical garden as well in the park and the square (h = 16.3–17.2 m; D = 26.0–28.3 cm) and substantially less than the trees, plantations are located near the steel mills (h = 11.9–12.6 m; D = 20.9–23.9 cm). Trees in these plantations have the vo lume of the crown in 3.7–4.1 times smaller, the average life status in 2.4–2.6 times lower than in comparison with the plants in the arboretum and 61.7 % of the trees in plantations in the emission zone of metallurgical combines have the dieback. The main type of B. pendula plantings is clumb of trees, where plants were planted in most cases at a distance of 0.5–4.0 m; it causes significant inhibition of 23–35-year-old trees growing in the central parts of clumbs. Some of 35–40-year-old trees of B. pendula gradually loses its decorative effect due to the development of the dieback.